2022
DOI: 10.3389/fsoc.2021.741202
|View full text |Cite
|
Sign up to set email alerts
|

“Just Throw It Behind You and Just Keep Going”: Emotional Labor when Ethnic Minority Healthcare Staff Encounter Racism in Healthcare

Abstract: Encountering racism is burdensome and meeting it in a healthcare setting is no exception. This paper is part of a larger study that focused on understanding and addressing racism in healthcare in Sweden. In the paper, we draw on interviews with 12 ethnic minority healthcare staff who described how they managed emotional labor in their encounters with racism at their workplace. Data were analyzed using thematic analysis. The analysis revealed that experienced emotional labor arises from two main reasons. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
(69 reference statements)
4
13
0
Order By: Relevance
“…Racialized professionals' and trainees' experience of being deprioritized, over-looked and subject to overt racist abuse was commonplace and often interpreted as a lack of basic rights to be treated equally and to have qualifications, whether gained in Sweden or elsewhere, recognized. Some staff noted the emotional labour incurred by racism (Ahlberg et al, 2022), confirming earlier analyses (Evans and Moore, 2015), while others denied that discrimination was harmful to them, insisting that they could rise above it. The contested nature of gendered and racialized professional, ethnic and national identities is analysed here.…”
Section: Project Interview Materials In Generalmentioning
confidence: 63%
See 1 more Smart Citation
“…Racialized professionals' and trainees' experience of being deprioritized, over-looked and subject to overt racist abuse was commonplace and often interpreted as a lack of basic rights to be treated equally and to have qualifications, whether gained in Sweden or elsewhere, recognized. Some staff noted the emotional labour incurred by racism (Ahlberg et al, 2022), confirming earlier analyses (Evans and Moore, 2015), while others denied that discrimination was harmful to them, insisting that they could rise above it. The contested nature of gendered and racialized professional, ethnic and national identities is analysed here.…”
Section: Project Interview Materials In Generalmentioning
confidence: 63%
“…The lack of hospitality, in terms of welcoming strangers into clinical space, may be justified in terms of clinical priorities such as infection control and the protection of vulnerable patients. The association of medicine with the natural sciences means that clinical practice contributes to the reproduction of race as an absent presence (M’charek et al, 2014) and understanding hospitals as formerly exclusively White institutions contributes to making sense of the emotional labour (Ahlberg et al, 2022) that disproportionately burdens people of colour (Evans and Moore, 2015); emotional labour that is both gendered and racialized (Cottingham et al, 2018; Essed and Trienekens, 2008; Van Riemsdijk, 2010).…”
Section: Healthcare and Hospitalitymentioning
confidence: 99%
“…Implicit racial bias is associated with inequalities in treatment choices in regard to pain management, maternal care, diabetes care, end of life care and other treatment choices (Hamed et al, 2022 ). Ethnic minority staff also experience racism from both patients and other staff (Fowler, 2020 ; Stevens et al, 2012 ) and report lack of organizational support and space to discuss racism which results in stress and emotional depletion (Ahlberg et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the dilemma of gender equality and cultural diversity in Swedish healthcare encounters involves tensions between the values of cultural and religious diversity and liberal, individualistic values on sexual and reproductive rights matters [ 6 , 7 ]. By investigating values at the intersection of the individual, professional and policy levels, this study also contributes to research on structural asymmetries in healthcare access in Sweden and other European countries [ 8 ]. For example, qualitative studies have found indications of ethnic minority healthcare staff and healthcare users experiencing racism in Swedish healthcare [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating values at the intersection of the individual, professional and policy levels, this study also contributes to research on structural asymmetries in healthcare access in Sweden and other European countries [ 8 ]. For example, qualitative studies have found indications of ethnic minority healthcare staff and healthcare users experiencing racism in Swedish healthcare [ 8 ]. In multicultural consultations in women’s healthcare, HCPs’ awareness of their own values and patients’ values is of great importance for successful consultations by preventing misunderstandings and thus suboptimal care [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%